Occupational accident experience: Association with workers' accident explanation and definition - Silva, S.A.; Lima, M. L. (Safety Science, 2008)
Problem: The experience of an occupational accident, as a harmful and unexpected event, may elicit a process of construction of meaning. However, research has provided inconsistent results regarding to the role of such an experience in posterior sense-making. This article aims at understanding the association of an occupational accident experience with the explanation and definition given by workers for such events. Method: Fifty-six semi-structured interviews were conducted with workers from several sectors. This data was subject to content analysis and HOMALS (Multiple Correspondence Analysis). Results: An accident experience was associated with defensive explanations (focused on causes external to workers) and defensive definitions (highlighting the sudden nature of accidents and organizational weaknesses). Discussion: The study of the construction of meaning about accidents and its variability is highly relevant for understanding posterior preventive behavior and the accuracy in the report of future occupational accidents. Impact on industry: Organizations should be aware of discrepancies in conceptions and interpretations among employees about occupational accidents when planning prevention programs or improvement of accident data registration.